LINGUISTIC TENDENCIES OF ANOREXIA NERVOSA ON SOCIAL MEDIA USERS FACEBOOK (PRAGMATIC STUDY) - Wincana, Gita; Rahmat, Wahyudi; Tatalia, Ricci Gemarni (Journal of Pragmatics and Discourse Research, 2022)
This research is motivated by the large number of facebook users who express their discomfort with body shape and after further review, the discomfort expressed is included in the characteristics of people who have a tendency to anorexia nervosa. This study was conducted to describe the linguistic tendency of anorexia nervosa on facebook social media users, especially on the "MinuteVideos Indonesia" account based on the characteristics of anorexia nervosa tendencies seen from the form and meaning of the language conveyed. This type of research is a qualitative research using descriptive method. The data of this study is the linguistic expressiveness of facebook users who have anorexia nervosa tendencies in comments on the "MinuteVideos Indonesia" account. Data were collected using the free-of-charge listening technique (SBLC) and note-taking techniques. The data were analyzed using the matching method and the agih method. Based on the results of the study found thirteen types of expressive speech acts used by Facebook users who have anorexia nervosa tendencies in comments on the "MinuteVideos Indonesia" account and each of these utterances has a referential meaning. The tendency of anorexia nervosa is dominantly experienced by women. However, from the data obtained there are also men who experience anorexia nervosa tendencies.